Preliminary analysis on the effect of rain attenuation on Free Space Optics (FSO) propagation measured in tropical weather condition - Ahmad Zabidi, Suriza; Al-Khateeb, Wajdi Fawzi Mohammed; Islam, Md. Rafiqul; Naji, Ahmed Wathik (2011)
Free Space Optics (FSO) as potential high speed connectivity has capability similar to fiber optic in term of speed and bandwidth. The advantages of FSO over fiber are time and cost of deployment. However, since the transmission medium of FSO is atmosphere, atmospheric scattering is the major cause for interruption of FSO link. In temperate region, fog is the main factor that affects the availability of the link. However, in tropical region non-selective scattering is expected to be the major drawback. Non-selective scattering is wavelength independent and exists due to rainfall. In country like Malaysia rain season with heavy rain can reduce the received power of FSO link to below the threshold. In this paper the preliminary analysis is presented for the use in the larger scale to construct the tropical rain attenuation model for FSO. The result from the analysis showing that heavy rain will cause the attenuation of the link however the 99.999% is still achievable for the FSO system under Malaysia weather condition.